Biochemical changes in chickpea genotypes resistant and susceptible to grey mould - and MAHENDRA PAL, NEENA MITIER. J.S. GREWAL (Indian Phytopathology, 2002)
Healthy chickpea plants of genotype ICC 1069, resistant to Botrytis cinerea, had significantly lower total soluble sugars and free amino acids but higher total phenol levels than the susceptible genotype BGM 408, irrespective of the plant part tested. The amount of sulfur-containing amino acids, methionine and cystine was almost double in the resistant genotype compared with the susceptible genotype. Shoot tips had higher quantities of sugars and free amino acids but lower phenol contents compared with the middle and lower leaves, irrespective of the genotype. Sugars and phenols decreased after inoculation by B. cinerea. The decrease in phenols was more in susceptible genotype BGM 408 but the sugar content declined markedly in resistant genotype ICC 1069. The free pool of amino acids increased by 280% in BGM 408 after inoculation compared with only 22% in ICC 1069. All the amino acids except aspartic acid decreased after inoculation.